FRI0211 A descriptive analysis of real-world treatment patterns of innovator infliximab (REMICADE) and biosimilar infliximab in a treatment naÏve turkish rheumatologic disease population. (15th June 2017) - Yazici, Y; Xie, L; Ogbomo, A; Parenti, D; Goyal, K; Teeple, A; Ellis, L; Simsek, I
Abstract : Objectives: This retrospective healthcare claims analysis examined treatment patterns of innovator infliximab (IFX) and biosimilar infliximab (CT-P13) in a Turkish rheumatologic disease population after CT-P13 availability in July, 2014. Methods: Adult patients (pts) with ≥1 diagnosis code (ICD-10-CM) for rheumatoid arthritis (RA) were identified in a national Turkish healthcare database during the study period (01DEC2010–01DEC2015). Eligible pts had continuous medical/pharmacy enrollment ≥12 months before and ≥6 months after IFX or CT-P13 initiation (index date). Patients were naïve to IFX or CT-P13 (i.e. had no IFX or CT-P13 within 12 months before the index date). Demographics, concomitant diseases and medications, and treatment patterns, eg., dose, interval, discontinuation, and switch were summarized. Confirmed discontinuation was defined as a switch to another biologic medication or the absence of an index biologic claim for ≥120 days without censoring. Results: Key results are shown in the Table. A total of 1044 patients initiated either medication. The majority (80%; n=831) initiated IFX. The IFX cohort had a mean age of 42 years; 56% were women and mean follow up was 12 months. The CT-P13 cohort consisted of 213 pts with mean age of 43 years; 58% women; and mean follow up of 9 months. Approximately one-third of pts in each cohort had a concomitant diagnosis of ankylosing spondylitis (AS; TABLE). Other concomitant diseases and medications appeared balanced between cohorts. Pts in the IFX cohort had an average of 5.2 infusions and mean dose of 4.7 vials per infusion approximately every 8 weeks. Pts in the CT-P13 cohort had an average of 3.6 doses and mean dose of 5.8 vials per dispensing approximately 9 weeks apart. A confirmed discontinuation occurred in 55% of the IFX cohort; driven in part by switching. 24% of IFX pts had ≥1 biologic switch with 8% initially switching to CT-P13. Time to any discontinuation or censoring of IFX is shown in the Table. In the CT-P13 cohort, a confirmed discontinuation was observed in 63%; 31% switched to another biologic therapy; and 20% initially switched to IFX. Time to any discontinuation or censoring of CT-P13 is shown in the Table. Conclusions: These findings in a single country indicate that real world utilization patterns may differ between innovator IFX and CT-P13, with predominantly more patients initiating IFX; greater overall CT-P13 discontinuation and a higher proportion of patients switching from CT-P13 to IFX. Further studies are needed to understand the reasons for these observed differences. Disclosure of Interest: Y. Yazici Grant/research support from: Janssen Scientific Affairs, LLC, L. Xie Consultant for: Janssen Scientific Affairs, LLC, A. Ogbomo Consultant for: Janssen Scientific Affairs, LLC, D. Parenti Employee of: Janssen Scientific Affairs, LLC, K. Goyal Employee of: Janssen Scientific Affairs, LLC, A. Teeple Employee of: Janssen Scientific Affairs, LLC, L. Ellis Employee of: Janssen Scientific Affairs, LLC, I. Simsek Grant/research support from: Janssen Scientific Affairs, LLC